Analysis of mechanical vibration of a servomotor using vibrometry - Olejárová, Štefánia (Journal of Production Engineering, 2023)
The servomotor must ensure resistance to the environment (mechanical vibration, humidity, temperature) in which it will be operated. It is the vibration that is one of the important monitored parameters that allow obtaining initial information about the operational status of the equipment. Exceeding the preset limits adversely affects the service life and reliability of the components. The experimental part is focused on recording and analyzing the magnitude of vibration acceleration, through frequency spectrum and its comparison with the envelopes of frequency spectrums. The obtained graphical dependencies from the experiments are a suitable basis for the assessment of the objective state.